An analysis of directive speech acts in the text of Jumanji: the next level movie directed by Jake Kasdan - Putri Zuliana Zal Zabella; Dias Andris Susanto; Arso Setyaji (Indonesian Journal of Education and Pedagogy, 2025)
Directive speech acts are crucial in effective communication, particularly in educational and cinematic contexts, where language functions are dynamically expressed. However, limited research still explores directive speech acts in movie scripts as authentic materials for language learning. This study aims to analyze directive speech acts in the movie Jumanji: The Next Level by identifying their types, describing how they are actualized, and explaining the meanings behind their use. Searle’s theory of speech acts served as the theoretical foundation. This research employed a descriptive qualitative method. The data were collected through documentation techniques, carried out in the following steps: (1) downloading the movie, (2) watching and understanding it carefully, (3) focusing on the characters’ dialogues, (4) reading and selecting relevant utterances while numbering them, and (5) identifying and classifying the selected dialogues based on the types of directive speech acts. The results show that there are five types of directive speech acts in the movie. From a total of 506 utterances, the researcher identified the following distribution: 247 questioning utterances (48.8%), 192 commanding utterances (38.0%), 35 forbidding utterances (6.9%), 24 requesting utterances (4.7%), and 8 permitting utterances (1.6%). Among these, questioning is the most dominant type. Moreover, the meaning of directive speech acts in Jumanji: The Next Level is strongly influenced by the situational context. The presence of numerous missions to be completed plays a significant role in the frequent use of questioning speech acts, as these situations require information to be obtained. Throughout the dialogues, characters rely on questioning to guide conversations and solve the problems that arise.